Are data available for tracking progress on nutrition policies, programs, and outcomes in Nepal? - Neupane, Sumanta; Jangid, Manita; Scott, Samuel P.; Nguyen, Phuong Hong; Kim, Sunny S.; Murira, Zivai; Torlesse, Harriet; Menon, Purnima (International Food Policy Research Institute, 2021)
The World Health Organization (WHO) and other global nutrition and health agencies recommend nutrition actions throughout the life-course to address malnutrition in all its forms. In this report, we examined how Nepal’s nutrition policies and programs addressed recommended nutrition actions, nutrition outcomes, and the determinants of these outcomes. We reviewed population-based surveys and administrative data systems in order to assess the data availability on nutrition actions, and on the indicators of determinants and outcomes. Our review identified a total of 53 recommended evidence-based nutrition actions, of which 50 nutrition actions were applicable in Nepal. Of these, 45 were addressed in the country’s nutrition policies and programs and some of the actions were only available in some districts. Nutrition actions that were not included in current policies and programs included calcium supplementation and advice on consuming calcium during pregnancy, and daily iron and folic acid (IFA) supplementation during childhood. Current policies addressed daily or intermittent IFA supplementation during preconception and food supplementation for malnourished lactating women during the postnatal period; however, there was no program to implement these actions. Nepal’s Multi-Sector Nutrition Plan (MSNP) recognized and addressed all key determinants of nutrition; it also expressed an intent to address all SDG nutrition targets for maternal, infant, and young child nutrition. Noncommunicable diseases (NCDs), however, were addressed separately by a multisectoral plan for NCDs. Our data review found that out of 45 actions that policies and programs addressed, population-based surveys contained data on only 27 actions and administrative data systems contained data on only 25 actions. Population-based surveys and administrative data sources contained no data on: food supplementation during adolescence; weight monitoring and various types of counseling during pregnancy; optimal timing (delayed) of umbilical cord clamping, support for breastfeeding and immediate skin-to-skin contact, optimal feeding of low-birth-weight infants and counseling of mothers of low-birth-weight infants on kangaroo mother care (KMC) during delivery and in the postpartum period; breastfeeding counseling, counseling on appropriate complementary feeding, counseling after growth monitoring, and inpatient management of severe acute malnutrition (SAM) during early childhood. Population-based surveys contained data on most of the indicators of immediate and underlying determinants, while administrative data systems did not have data on all indicators of immediate determinants. Data on all indicators of nutrition outcomes were available from population-based surveys. In conclusion, Nepal’s and program landscape for nutrition is robust, however the gaps in data availability for tracking progress on nutrition actions are much larger than the gap in policies and programs for addressing recommended actions. Future population-based surveys and modifications of administrative data systems should aim to fill the identified data gaps for nutrition actions.